ENHANCING THAI TEACHER'S TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE FOR STEM EDUCATION WITH IPAD - Chatmaneerungcharoen , Siriwan (Journal of Education and Innovation, 2024)
The objectives of this research were as follows: 1) To compare Thai teachers' Technological Pedagogical Content Knowledge (TPACK) for STEM education using iPads before, during, and after participating in a teacher professional development program; 2) To compare the perception and understanding of Thai teachers in STEM regarding the use of digital technology tools; 3) To develop STEM education teaching and learning using digital technology tools and iPads; and 4) To establish continuous coaching for educational supervisors and administrators. This research employed a mixed methods approach with research participants including science teachers, math teachers, technology teachers, administrators, and supervisors from 148 schools. Data collection tools included self-assessment surveys on knowledge in content, teaching methods, and technology, assessments of STEM lesson plans, questionnaires on teachers' perception and usage of digital technology tools, semi-structured interviews, classroom observations, and reflective journals as part of Professional Learning Communities (PLCs). Data analysis included descriptive statistics and inductive methods. The findings revealed that the majority of teachers (89.04%) had a positive perception that using digital technology tools can enhance students' creative thinking and communication skills; 2) The knowledge development in instructional content and technology of teachers increased through evaluating the design of lesson plans and teaching practices after participating in the professional teacher development program; 3) 83.56% of teachers' teaching practices showed a significant correlation with the use of digital technology; 4) The results with administrators and educational supervisors who support teachers' teaching practices in the roles of managers and intellectual coaches using a continuous support format combined with classroom observation.